A strategic conflict analysis in IT outsourcing using the graph model for conflict resolution. Issue 6 (20th April 2020) - Silva, Maisa Mendonça; Poleto, Thiago; de Gusmão, Ana Paula Henriques; Costa, Ana Paula Cabral Seixas
Abstract : Purpose: The purpose of this paper is to propose a strategic conflict analysis, based on the graph model for conflict resolution (GMCR), that is applied to information technology outsourcing (ITO) in a real-world software development and implementation process in Brazil. Design/methodology/approach: Because the idea of this study is to answer "why" the ITO conflicts occur and "how" they can be avoided, the case study methodology was adopted. The software GMCR II was used to analyze the interactions between an IT vendor and an IT client. Findings: The results suggest that a lack of relational governance is a critical issue that could be handled to improve the interaction between those involved. Research limitations/implications: The main results are restricted to the case study and cannot be generalized. Moreover, a specific limitation of this paper pertains to the use of the GMCR and the consequent difficulty for IT vendors and IT clients to work with a large number of actions and to set preferences for several states of conflict. Practical implications: The strategic analysis of outsourcing conflicts provides a holistic view of the current situation that may assist the client and vendor in future decisions and identify guidelines to ensure successful ITO. Therefore, this paper provides an effective guide for clients and vendors to better manage conflicts and establish a contingency vision to avoid such disputes. Originality/value: The ITO conflict is analyzed using the GMCR, considering both perspectives of the outsourcing process (vendors and clients).